Evaluasi Dampak Kebijakan Kurikulum Merdeka Di Madrasah Aliyah Negeri 1 Tabalong: Studi Kasus Madrasah Piloting - Sarury, Jiabus; Irawanto; Akos, Misransyah; Priono, Singgih (STIA Bina Banua Banjarmasin, 2025)
ABSTRACT This study aims to evaluate the impact of the Merdeka Curriculum policy and the perceptions of teachers, students, and parents at MAN 1 Tabalong. Using a qualitative case study method, the research involved five key informants, including the acting head of the madrasa, the vice principal for curriculum, and teachers. The findings indicate that the Merdeka Curriculum has been effectively implemented in terms of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy, though challenges remain. These challenges include uneven achievement of student competencies, the need for continuous support, and improvements in infrastructure and facilities. Increased budget allocation is also necessary for optimal implementation. Teachers appreciate the curriculum's flexibility, enabling learning tailored to students' needs and local contexts. Students enjoy active learning through projects aligned with their interests, while parents support the curriculum, viewing it as a comprehensive approach to fostering their children's potential. ABSTRAK Penelitian ini bertujuan mengevaluasi dampak kebijakan Kurikulum Merdeka serta persepsi guru, peserta didik, dan orang tua di MAN 1 Tabalong. Menggunakan metode kualitatif studi kasus, penelitian melibatkan lima informan, termasuk kepala madrasah, wakil bidang kurikulum, dan guru. Hasilnya menunjukkan bahwa Kurikulum Merdeka berjalan baik dari segi efektivitas, efisiensi, kecukupan, pemerataan, responsivitas, dan ketepatan, meski menghadapi tantangan seperti pencapaian kompetensi yang belum merata, kebutuhan pendampingan berkelanjutan, serta peningkatan sarana dan prasarana. Dukungan anggaran juga penting untuk optimalisasi. Guru mengapresiasi fleksibilitas kurikulum yang memungkinkan pembelajaran berbasis kebutuhan peserta didik dan kondisi lokal. Peserta didik menikmati pembelajaran aktif melalui proyek sesuai minat, sementara orang tua mendukung karena kurikulum ini dinilai mampu mengembangkan potensi anak secara lebih menyeluruh.